Vector space search engines that maximise expected user utility. (16th April 2009) - Ferhatosmanoglu, Nilgun; Allen, Theodore T.; Canahuate, Guadalupe
Vector space methods are perhaps the most widely studied type of search engine. Yet, these search engines are generally not optimal in the sense that the search results are based on the current query and the available database without considering information about the user preferences. This article establishes a rigorous relationship between the tuning of dimensional weights and the maximisation of the expected utilities of users. The methods can be implemented using standard software for discrete choice analysis and readily available data. The proposed methodology is called 'discrete choice analysis weighting' (DCAW). The test-bed evaluation of DCAW conducted on around 10, 000 news data offers promising results for further studies. Also, several opportunities for future research are proposed.